تأثير تمرينات الهيبوكسيك باستخدام القناع التدريبي في تطوير بعض المتغيرات الفسيولوجية وإنجاز ركض 800 متر للناشئين - أحمد، كاوه محمود; ميرزا، طارق أحمد (جامعة القادسية - كلية التربية الرياضية, 2018)
يهدف البحث إلى إعداد تمرينات الهيبوكسيك باستخدام القناع التدريبي، وكذلك التعرف على تأثير تمرينات الهيبوكسيك باستخدام القناع التدريبي في تطوير بعض المتغيرات الفسيولوجية وإنجاز ركض ٨٠٠ م لعينة البحث. استخدم الباحثان المنهج التدريبي لتحقيق أهداف البحث، واجري البحث على عينة من لاعبي نادي (بيشمركه) بألعاب القوى/ فئة الناشئين (١٧ - ١٦) سنة للموسم الرياضي (٢٠١٦ - ٢٠١٧) بفعالية ركض ٨٠٠ م البالغ عددهم (٨) عدائين، وهم يمثلون مجتمع البحث بالطريقة العمدية، وتم استبعاد (عدائين)، وذلك لعدم انتظامهم في الحضور إلى التمرين، وبذلك بلغت عينة البحث (٦) عدائين يمثلون نسبة (75%) من المجتمع الأصلي، وتم تطبيق مفردات هذا المنهاج على المجموعة التجريبية وبواقع ثلاثة أيام في الأسبوع، أيام (السبت والإثنين والأربعاء) ولمدة ستة أسابيع وبذلك يصبح العدد الكلي للوحدات التدريبية (١٨) وحدة، وطبقت المجموعة الضابطة التدريبات المعتادة، وبعد إجراء الاختبارات البعدية توصل الباحثان إلى الاستنتاجات الآتية: إن استخدام القناع التدريبي كوسيلة تعيق عملية التنفس في أثناء التدريب كان له أثر في إحداث نقص في كمية الأوكسجين المستنشق. إن استخدام القناع التدريبي وسيلة إعاقة للتنفس بالتدريب، أسهم وبنجاح في إحداث التغييرات الوظيفية لدى العدائين وتطوير اختبارات البحث. كان لاستخدام طريقة التدريب الفتري مرتفع الشدة بمنهج تدريبات الهيبوكسيك، الأثر الواضح في تحسن مستوى الإنجاز لركض ٨٠٠ متر. أظهرت النتائج البعدية أن نسبة التطور لدى أفراد المجموعة التجريبية كانت أكثر تطوراً من أفراد المجموعة الضابطة ولجميع الاختبارات. إن تدريبات الهيبوكسيك تعطي نتائج إيجابية وتكيفات فسيولوجية أسرع من التدريب العادي.
The research aims at knowing: - Preparation of hypoxic exercises using the (Training Mask 2.0). -Identification of the effect of hypoxic exercises using the training mask in the development of some physiological variables and the achievement of running 800 meters for juniors. Method of the study: The researchers used the training curriculum to achieve the research objectives. We separated the participants to (Experimental - Control) groups and all participants were athlete from (Peshmerga club/ Track and field) in Sulaimany governorate. The participants age were from (16-17) years old for (2016-2017) session who are 800 meter runners, included the each group (4 participants), excluded two runners from the study experiment by reason of lack of attendance in the training. Thus, we conducted the study on six athletes, who were representing (%75) of the original community. Participants attempt the study from three days during six weeks which equalised (18 training units) and the control group conducted their usual training. Conclusion: Using hypoxia training mask obstructed the process of breathing and this reduces the amount of oxygen in the inhalation progress. Utilising hypoxia training mask contributed to change physiological functions successfully. The high interval intensity training with using hypoxia training mask improve (800 meter runners) ability and the time period achievements. The results showed that the experimental group improved their performance compared with control group. The experimental group by using hypoxia training adapt their physiological function comparing with control group with their usual training.
Keywords: التربية البدنية -- التمرينات الرياضية -- تمرينات الهيبوكسيك -- المتغيرات الفسيولوجية -- الناشئون الرياضيون